2016
DOI: 10.1002/jctb.5058
|View full text |Cite
|
Sign up to set email alerts
|

An economic model for estimating the viability of biodiesel production fromJatropha curcasL.

Abstract: BACKGROUND: At commercial level, the biodiesel production process is well established for many types of feedstock. However, economic feasibility depends on regional fluctuating data, making each case unique. A calculation model to analyze the economic feasibility of biodiesel production from Jatropha curcas was developed, along with an analysis of the energetic balance derived from this process. RESULTS: Yucatán state has the cultivation surface to replace 10% of its fossil diesel fuel consumption with biodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…However, Jatropha is considered an emergent commercial crop, and there is not enough information about cultivation and production cost [21]. There have been a great number of LCAs for Jatropha curcas, some of them not including land-use change (LUC); other studies found that LUC can be more useful in determining the carbon balance [22].…”
mentioning
confidence: 99%
“…However, Jatropha is considered an emergent commercial crop, and there is not enough information about cultivation and production cost [21]. There have been a great number of LCAs for Jatropha curcas, some of them not including land-use change (LUC); other studies found that LUC can be more useful in determining the carbon balance [22].…”
mentioning
confidence: 99%
“…For example, Wang, Calderon, and Lu () calculated the cost of Jatropha seed production to be 2.4 × 10 4 CNY t −1 year −1 , accounting for 88.4% of the full‐chain costs of Jatropha biodiesel production in China with a seed yield assumption of 1,485 kg ha −1 year −1 , and the study indicates that financial breakeven on this yield level cannot be achieved based on the market price of the biodiesel. Navarro‐Pineda, Ponce‐Marbán, Sacramento‐Rivero, and Barahona‐Pérez () concluded that the biodiesel–jatropha chain is not economically viable with a seed productivity of 1,495 kg ha −1 year −1 in Mexico, with field labor being the major cost, accounting for 64.3% of the total biodiesel cost. Seed yield and mechanization need to be improved to achieve a positive net present value.…”
Section: Introductionmentioning
confidence: 99%
“…However, most previous works studied individual processes for valorizing one fraction of the jatropha biomass at a time, not considering the integration of processes in a whole‐crop biorefinery. Furthermore, most of the studies evaluating the impacts of bioenergy from jatropha biomass consider energy, economic, or environmental factors independently, and did not include a holistic sustainability approach …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, most of the studies evaluating the impacts of bioenergy from jatropha biomass consider energy, economic, or environmental factors independently, and did not include a holistic sustainability approach. [14][15][16][17] This study reports the conceptual design integrated with sustainability criteria for a biorefinery plant for processing jatropha fruits. The objective of this work was to confirm whether a biorefinery configuration improves the overall sustainability of the plant design, compared to a typical biodiesel production configuration.…”
mentioning
confidence: 99%